Novel optical solitary waves and modulation instability analysis for the coupled nonlinear Schrodinger equation in monomode step-index optical fibers - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi; Baleanu, Dumitru (Academic Press Ltd- Elsevier Science Ltd, 2018)
This paper addresses the coupled nonlinear Schrodinger equation (CNLSE) in monomode step-index in optical fibers which describes the nonlinear modulations of two monochromatic waves, whose group velocities are almost equal. A class of dark, bright, dark bright and dark-singular optical solitary wave solutions of the model are constructed using the complex envelope function ansatz. Singular solitary waves are also retrieved as bye products of the in integration scheme. This naturally lead to some constraint conditions placed on the solitary wave parameters which must hold for the solitary waves to exist. The modulation instability (MI) analysis of the model is studied based on the standard linear-stability analysis. Numerical simulation and physical interpretations of the obtained results are demonstrated. It is hoped that the results reported in this paper can enrich the nonlinear dynamical behaviors of the CNLSE. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Complex envelope function ansatz; Modulation instability; Solitary wave; Coupled nonlinear Schrodinger equation